Place of physical training in the task psychological training of servicemen. - Gysak O.D; Romanchuk S.V (Kharkov National Pedagogical University, 2011)
The article exposed the use of forms of physical training for the formation of psychological readiness to act in military training and battlefield. Analysis of pedagogical, psychological and special literature, the analysis features of professional military airborne troops, and suggested areas of application of lessons on overcoming obstacles to the formation of the psychological readiness of military personnel.